Nurturing National Dual Training System towards government-link companies’ (GLCs) standard - Minghat, Asnul Dahar; Mustakim, Siti Salina; Wu, Mingchang; Siswanto, Ibnu (Istanbul Kultur University, 2018)
It has been thirteen years since National Dual Training System (NDTS) was introduced and implemented as a training system with the potential to produce human capital that is labeled as knowledge worker (k-workers). Trainees will undergo 70% hands-on training in work environment and 30% theories at training centers. Not only talents needed by industries are produced, trainees are also getting early exposure to the real work. This paper discusses the strength of the dual system implemented in industries. In order to fulfill the mission, strategy, and thrusts of the Training Master Plan for Occupational Skills Development, three aspects of enhancement were listed, (1) full utilization of the Human Resource Development Fund (HRDF), (2) enforcement of specific laws strictly and prudently for the smooth implementation, and (3) making full use of the research information, obtain for the purpose of long-terms solutions in NDTS implementation.